2007
DOI: 10.1186/1477-7819-5-56
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and patterns of care for invasive breast carcinoma at a community hospital in Southern India

Abstract: Background: Breast cancer incidence in India is on rise. We report epidemiological, clinical and survival patterns of breast cancer patients from community perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
44
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 15 publications
10
44
0
Order By: Relevance
“…After careful and thorough reading, 4 articles have been again excluded for the following reasons Full text article not available (1), Not from South India (1), Study on Families of BC patients (1), and educational intervention on screening (1). Finally 16 articles have been selected for the qualitative synthesis (Gajalakshmi and Shanta, 1991;Nandakumar et al, 1998;Yeole and Kurkure, 2003;Kuraparthy et al, 2007;Ali et al, 2008;Mathew et al, 2008;Syamala et al, 2008a;2008b;Dey et al, 2009;Jayalekshmi et al, 2009;Syamala et al, 2009;Vaidyanathan et al, 2009;Harrison et al, 2010;Surekha et al, 2010;Chauhan et al, 2011) Methodological qualities of included studies: Out of 16 included studies 10 were Case studies, 1 Nested case control study (on a cohort of women), 4 studies were based on Secondary data analysis and 1 (Marmot et al, 2007) was cross-sectional study. Confounding factors were reported and adjusted in 2 out of 10 case control studies, mentioned and not controlled in 3 studies and not mentioned in rest of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…After careful and thorough reading, 4 articles have been again excluded for the following reasons Full text article not available (1), Not from South India (1), Study on Families of BC patients (1), and educational intervention on screening (1). Finally 16 articles have been selected for the qualitative synthesis (Gajalakshmi and Shanta, 1991;Nandakumar et al, 1998;Yeole and Kurkure, 2003;Kuraparthy et al, 2007;Ali et al, 2008;Mathew et al, 2008;Syamala et al, 2008a;2008b;Dey et al, 2009;Jayalekshmi et al, 2009;Syamala et al, 2009;Vaidyanathan et al, 2009;Harrison et al, 2010;Surekha et al, 2010;Chauhan et al, 2011) Methodological qualities of included studies: Out of 16 included studies 10 were Case studies, 1 Nested case control study (on a cohort of women), 4 studies were based on Secondary data analysis and 1 (Marmot et al, 2007) was cross-sectional study. Confounding factors were reported and adjusted in 2 out of 10 case control studies, mentioned and not controlled in 3 studies and not mentioned in rest of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Previous Indian studies have documented that rates of ER negativity is high among breast cancers in Indian women [2][3][4]. It has been suggested that factors contributing to this high ER negativity could be technical failures of detection of ER, younger age of patients, and advanced stage at presentation -all of which can increase the proportion of ER negative tumours [2].…”
Section: Discussionmentioning
confidence: 99%
“…lacking ER, progesterone receptor (PR) as well as HER-2 receptors [1]. Previous data from India show higher proportion of ER negative breast cancer compared to the west [2][3][4]. This higher burden of ER negative disease has been attributed to several factors, including technical failures at detection of ER positivity, younger age of patients, and advanced stage at presentation -all of which can increase the proportion of ER negative tumours [2].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly the biological behaviour and treatment factors affecting outcome are less commonly reported than breast malignancies of epithelial origin 3 . Furthermore there are a great number of varying histopathological subtypes that can affect the breast 4 , the commonest histopathological subtypes being malignant phyllodes tumour 5,6 and angiosarcoma 7 .…”
Section: Introductionmentioning
confidence: 99%